Excelência no serviço público: uma proposta de planejamento e controle das finanças públicas - Vargas, Rosaura de Fátima Oliveira de (2004)
The present paper has the objective of analyzing of the municipal takings, presenting proposals to improve them, in a way to minimize the shortage of financial resources faced by the municipal public manager. On the other hand, after conceptualizing the expenditures and shoeing where the municipal public resources are applied, it is suggested the application of a cost system to be used by the Brazilian Municipalities. The study fundaments is based in the Brazilian Tributary System, under the plight of the Federal Constitution, in the Law 4320/64, base of the public accounting, in the bibliographical exploratory research in secondary data. The sample contemplates the ten most populated Municipalities of Rio Grande do Sul, assessing the performance of their takings and tax-paying contributive capacity of each municipality, with emphasis in the municipality of Santa Maria. The results obtained allow concluding that there is a huge idle capacity concerning the receiving of the municipal tributes. This fact is due to the unfamiliarity of the managers or, simply, the political unwillingness to implement the necessary actions that in a way may be considered unpopular measures, although of great contribution to the balance of the public accounts. Through the analysis of the expenses, the application of a cost system in the public management may cause a larger control and qualification of the public expenditure. In this sense, a larger professionalization of the public sector is aimed in what refers to the strategic planning of the municipal resources.